Secondary School Students’ Attitudes Toward Teaching and Learning of Feminist Literature in Kenya - Simwa, Solomon Ashiono (Advances in Social Sciences Research Journal, 2017)
ABSTRACT Patriarchy in many societies has disadvantaged women in education, economic activities and leadership. The feminist movement is a major avenue through which women and other human rights activists seek to rectify this situation. However, due to opposition from those who would like to maintain the status quo, the goals of feminism are not always easy to achieve. This scenario is reflected in some works of literature studied in Kenyan secondary schools. This paper highlights students’ attitudes towards teaching and learning of feminist literature in Lugari area of Kenya. Data were collected using a self-developed and structured questionnaire. Frequency counts and percentages reveal that feminist literature has minimal positive impact on students’ attitudinal development in terms of gender equality. Also, most students prefer male to female teachers teaching them feminist literature due to weaknesses related to female teachers as well as patriarchal backgrounds of the students.